Knowledge, attitudes and barriers of nurses on benefits of the quality of patient record-keeping at selected public district hospitals in Burundi - Edison Bizimana; Million Bimerew (Elsevier, 2021)
The study examined the patient record-keeping knowledge, attitudes and barriers of nurses on benefits of the quality of patient record-keeping in two hospitals in Burundi. A quantitative descriptive survey design with a self-administered questionnaire was used to collect data from 121 nurses at two public district hospitals. The results show 82.6% (n = 100) of nurses scored > 80% on the scale of knowledge indicating adequate knowledge; 17.4% (n = 21) of nurses scored < 80%, indicating insufficient knowledge. Regarding attitudes, 64% (n = 78) of nurses scored > 80% on the attitudes scale, while 36% (n = 43) scored < 80%, indicating negative attitudes. Barriers contributing to poor quality of patient record-keeping were lack of training on record-keeping (81.3%, n = 99), excessive work load, demotivation (81.3%, n = 99), lack of time (46, n = 38%), and poor support by administrative policies (55.4%, n = 67). The Chi-square test show statistically there was a significant association between years of experience and respondents' knowledge on benefits of the quality of patient record-keeping (χ2 = 19.182, p = .000724). On the attitudes scale the Chi-square test shows that level of education was significantly associated with respondents' attitudes on benefits of the quality of patient record-keeping (χ2 = 22.674, p = .001). The study demonstrated that although there was adequate knowledge and positive attitudes on benefits of the quality of patient record-keeping, there were barriers contributed to poor quality of patient record-keeping in the selected hospitals. Gender, and years of experience as well as level of education was significantly associated with nurse's knowledge on benefits of the quality of patient record-keeping. Implications of the findings were discussed.